Mata Kuliah Pendidikan Mitigasi Bencana Berbasis Riset Pencegahan Longsor Lahan dengan Cara Vegetatif - Sutomo Sutomo; MA. Miftahuddin; Ahmad Ahmad (UM Purwokerto Press, 2022)
This study aims to determine the impact of research-based learning on disaster mitigation education courses for students of the Geography Education study program at the Muhammadiyah University of Purwokerto. The method used is a survey of students both before learning and after learning. While the data analysis technique used qualitative analysis. The results obtained from this study are students can understand knowledge and attitudes in dealing with disasters, can understand disaster policies and guidelines, can understand disaster emergency response plans, and can understand disaster early warning systems.